Cost-effective analysis of mechanical thrombectomy (MT) in patients with poor baseline modified Rankin Score (mRS). (May 2022) - Haranhalli, Neil; Fortunel, Adisson; Javed, Kainaat; Zampolin, Richard; Brook, Allan; Liberman, Ava; Lee, Seon-Kyu; Altschul, David; Schechter, Clyde
Highlights: Benefit of thrombectomy (MT) in patients with pre stroke disability is unknown. Purpose is to calculate cost impact of MT in patients with severe disability. We developed a Markov economic model with a life-time horizon analysis of costs. Marginal cost-effective ratio of 18, 835.00 for MT in minimal disability patients. Abstract: Mechanical thrombectomy (MT) has been established as a standard of care for patients with acute ischemic stroke for the past five years. However, the direct benefits of this treatment in patients with baseline disability remains unclear. This study aims to elucidate the cost impact of performing MT on patients with moderate-to-severe baseline disability to work towards an optimized system of care for acute ischemic stroke. We developed a Markov economic model with a life-time horizon analysis of costs associated with mechanical thrombectomy in patients grouped on baseline disability as defined by modified Rankin Score. Our clinical and economic data is based on an American payer perspective. Our results identified a marginal cost-effective ratio (mCER) of 18, 835.00 per quality-adjusted life year (QALY) when mechanical thrombectomy is reserved as a treatment only for patients with no-to-minimal baseline disability as compared to those with any level of baseline disability. Our results provide a framework for these future studies and highlight key sectors that drive cost in the surgical treatment and life-long care of patients with acute ischemic stroke.